E-116 Clinical characteristics, stroke mechanism and outcome of isolated symptomatic basilar artery stenosis. (22nd July 2019) - Samaniego, E; Shaban, A; Ortega-Gutierrez, S; Hasan, D; Derdeyn, C; Dai, B; Roa, J; Adams, H; Leira, E
Abstract : Background: While diffuse atherosclerotic disease affecting the posterior circulation has been described extensively, the prevalence, natural history and angiographic characteristics of isolated symptomatic basilar artery stenosis (ISBAS) remains unknown. Methods: We reviewed our prospectively acquired institutional database to identify patients with ≥ 50% symptomatic basilar artery (BA) stenosis without significant atherosclerotic burden in the vertebral or posterior cerebral arteries. Stroke mechanism, collateral circulation through the posterior communicating arteries, degree and length of the stenosis were analyzed. The primary outcome was time from index event to new transient ischemic attack (TIA), acute ischemic stroke (AIS) or death. Other outcome variables included modified Rankin scale (mRS) score on discharge and last follow-up. Results: Of 6369 patients with AIS/TIA, only 91 (1.43%) had ISBAS. Seventy-three (80.2%) patients presented with AIS and 18 (19.8%) with TIA. Twenty-nine (31.9%) were women and the median age was 66.8 ± 13.6 years. The mean follow-up time was 2.7 years. The most common stroke mechanism was artery-to-artery thromboembolism (50.8%), followed by perforator occlusion (32.3%) and flow-dependent/hypoperfusion (16.9%). The percentage of stenosis was lower in patients who had favorable outcome compared to those with mRS 3–6 on discharge (78.3 ± 14.3 vs 86.9 ± 14.5, p=0.007). Kaplan-Meier curves showed higher recurrence/death rates in patients with ≥ 80% stenosis, mid-basilar location and poor collateral circulation. Approximately 13% of ISBAS patients presented with complete BA occlusion. Conclusion: ISBAS is an uncommon (1.5%) cause of TIAs and AIS. Males in their sixties are mostly affected and artery-to-artery embolism is the most common stroke mechanism. Mid-basilar location, ≥ 80% stenosis and poor collateral circulation are important factors associated with worse prognosis. Keywords: basilar artery stenosis, ischemic stroke, transient ischemic attack, intracranial atherosclerotic disease, stroke mechanism, collateral circulation, posterior circulation. Disclosures: E. Samaniego: None. A. Shaban: None. S. Ortega-Gutierrez: None. D. Hasan: None. C. Derdeyn: None. B. Dai: None. J. Roa: None. H. Adams: None. E. Leira: None.